EVALUATION OF ANTIMICROBIAL AND SYNERGISTIC ANTIMICROBIAL PROPERTIES OF PTEROCARPUS SANTALINUS - Donga, Savan; Moteriya, Pooja; Chanda, Sumitra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The aim of the present study was to evaluate antibacterial and synergistic antimicrobial properties of leaf, stem and bark of Pterocarpus santalinus. Methods: The extraction was done by decoction method. The antimicrobial activity was done by agar well diffusion assay and the synergistic antimicrobial activity was done by agar disc diffusion assay.Â Results: The synergistic activity was studied with plant extracts plus antibiotics viz. Ampicillin , Polymyxin-B,Â Clotrimazole and Â Fluconazole.Â Conclusions: Amongst the three parts, the best antimicrobial activity was shown by bark extract. All the three parts showed synergistic antimicrobial activity with antibiotics but their level varied. Â The results suggest that all the three parts phytochemicals that enhance the antimicrobial efficacy of the antibiotics against some microorganisms and hence can be developed as a new therapeutic weapon against infectious diseases.